KERAGAMAN MAKANAN DAN KADAR GULA DARAH, KOLESTEROL SERTA ASAM URAT ANTARA KELOMPOK VEGAN DAN NON VEGETARIAN DI MAHA VIHARA MAITREYA CEMARA ASRI KECAMATAN PERCUT SEI TUAN DELI SERDANG TAHUN 2014 - karlina Listra; Mhd.Arifin Siregar; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Until now this degenerate disease like Diabetes, Hipercholesterolemia, Gout has been the cause of death in the world. This pattern of food is the most important key to ensure the health, one of them is vegetarian. From a check was commited to 6 of 10 people for a non vegetarian is the level of cholesterol and uric acid are high. The purpose of this research was to tell the diversity of food, blood sugar, cholesterol, and uric acid between the vegans and non vegetarian in Maha Vihara Maitreya Cemara Asri District Percut Sei Tuan Deli Serdang 2014. The kind of this research is observational in the study of latitude (cross sectional study). The population is vegans and non vegetarian. And collecting samples of purposive sampling with the number of samples are 30 people each group. Gathering data was done in an interview with food frequency method and to check a blood sugar, cholesterol and uric acid. The research shows that there’s a difference diet, vegans and non vegetarian, the average blood sugar respondents, which is 98,3 (sd 5,8) and in the non vegetarian average blood sugar 144,2 (sd 51,3); the average levels of cholesterol respondents, which is 142,9 (sd 27,3) and on the non vegetarian average cholesterol 222,0 (sd 32,7); the average levels of uric acid respondents, which is 4,8 (sd 0,7) and in the non vegetarian, average urric acid 6,2 (sd 1,5). Suggested vegans to maintain a diet and exercise to stay stablelike of blood sugar, cholesterol and uric acid, and for non vegetarian is expected to increase food vegetable like vegetables and fruit instead of animal food, other than that to do exercise regularly to keep health and avoid disease and degenerative. Keywords: Diversity of food, Blood sugar, Cholesterol, Uric acid, Vegans, Non Vegetarian